El proceso contable de la empresa comercial calzado guijarro del cantón Guano de la provincia de Chimborazo, período 2015 para la toma de decisiones. - Zavala Silva, Magaly del Rocío (2017)
The accounting process is a set of phases that compile and process information about a business, on which decisions will be made that will allow it to continue its activity and be competitive within the market. Based on the existence of a problem within the accounting aspects of the company, it was proposed as an objective of the investigation to identify how the accounting process influenced the decision making of the Guijarro Footwear Business Company of the Canton Guano of the Province of Chimborazo, During the period 2015. Its development began with the obtaining of general information of the company and fundamental theoretical aspects of each one of the variables, such as definitions, characteristics, phases and results. The deductive method was used because according to the general aspects of the accounting process and decision making a real situation within the company was inferred. The research was quasi-experimental; their field type, descriptive and correlational. Through observation, interview and survey information was obtained from the study population; Data that were analyzed to establish how the accounting process was related to the decisions taken during the 2014 period. The results show that the accounting process needs to be improved to achieve a better level of confidence. Key words: accounting process, decision making.